Report of Four Cases with Equestrian Injury: Therapeutic Approach and Outcome. (27th June 2018) - Oshima, Kiyohiro; Murata, Masato; Aoki, Makoto; Nakajima, Jun; Sawada, Yusuke; Isshiki, Yuta; Ichikawa, Yumi; Hagiwara, Shuichi
Abstract : Equestrianism is associated with a risk of severe trauma due to falls and/or direct injury from the horse, depending on the mechanism of injury. This article presents four cases of equestrian injury treated in Gunma University Hospital: Case 1: hepatic injury (fall and kick by the horse); Case 2: left hemopneumothorax and pulmonary contusion with multiple rib fractures (fall and trampling by the horse); Case 3: lumbar compression fracture (fall); and Case 4: scrotum injury (horse bite). Equestrian injuries may be high-energy traumas. Therefore, adhering to relevant primary care guidelines may prevent mortality by trauma.